Optimizing the structure of financial resources of industrial enterprises in the market economy mechanism - A. Vlasov; S. Ilukhina (Модернизация, инновация, развитие, 2016)
The article deals with the optimization of the structure of financial resources of industrial enterprises in the market economy mechanism. The slowdown of the Russian economy force companies to promote more accurate system financial planning its activities. In modern economic conditions the company's performance is largely dependent on the ability of management to more accurately predict financial flows, as well as more accurately predict the financial and human resources to ensure solvency of the enterprise, thus more competent to form the strategy of development of the organization.Goal / task. The aim of the article the search for the optimal structure of financial resources of industrial enterprises in the market economy mechanism and to develop proposals for the sustainable development of the enterprise. The task of this article is to investigate the structure of financial resources of the enterprise, in a deteriorating economic situation that must be considered in the sustainable development of industrial enterprises.Methodology. In conducting this study the main sources of the original data were the materials of the state statistics, the works of famous economists. The basis of the methodological developments based on comparative methods of analysis.Results. Given the concept of optimizing the structure of financial resources of the industrial enterprises. It shows the influence of external and internal factors affecting the stability of the industrial enterprises. Highlighted the impact of the economic situation on the role of these factors.Conclusions / significance. In the current economic conditions of the state and the new economic realities, it is necessary to focus to industrial enterprises to conduct an effective economic policy, thereby improving the financial stability of the enterprise.